Calcium absorption in rheumatoid arthritis. Issue 9 (September 1985) - Sambrook, P N; Abeyasekera, G; Ansell, B M; Foster, S; Gumpel, J M; Hill, P A; Reeve, J; Stevenson, J C
Abstract : Calcium absorption, assessed by a double isotope method, was found to be impaired in postmenopausal women with rheumatoid arthritis of recent onset (mean 14.2 months) compared with controls. Circulating levels of 1, 25-dihydroxyvitamin D (calcitriol) were higher than in controls, suggesting a primary malabsorption of calcium in these patients. The reduction in calcium absorption correlated with several measures of disease activity, suggesting that the disease process was responsible for the intestinal defect, but an effect from non-steroidal anti-inflammatory agents cannot be excluded. A primary reduction in calcium absorption may increase the risk of osteoporosis in women with rheumatoid arthritis.